MODEL PENGELOLAAN PASAR TRADISIONAL BERDASARKAN PEMASARAN DIGITAL ROGOWONGSO PATI - aditya aditya; Ariati Anomsari; Piji Pakarti; Awanis Linati Haziroh (Universitas Pasundan, 2025)
The development of digital technology and the internet has driven significant changes in consumer behavior, requiring traditional markets to adapt to remain relevant and competitive with modern markets and e-commerce. The purpose of this study was to find a traditional market management model based on digital marketing that is suitable for the Rogowongso Pati traditional market. This study used a quantitative method by distributing questionnaires to 157 traders at Rogowongso Pati Market. The analysis used PLS-SEM through SmartPLS version 3. The results showed that the use of e-commerce and training and digital literacy had a positive and significant effect on the success of market management, while the use of social media had no significant effect. In addition, government support strengthened the relationship between the use of e-commerce and the success of market management, but weakened the relationship between social media use and did not moderate the relationship between training and digital literacy on the success of market management. These findings confirm that the success of traditional markets in the digital era is more determined by the ability of traders to utilize e-commerce technology and digital literacy than simply using social media. This study recommends that the government focus on improving the digital capacity of traders through ongoing training, strategic assistance in the use of social media, and the provision of secure online infrastructure and payment systems.